2007
DOI: 10.2169/internalmedicine.46.1893
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Autoimmune Syndrome PossiblyCaused by Alpha Lipoic Acid

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 8 publications
(3 reference statements)
0
42
0
Order By: Relevance
“…These findings revealed a potential clinical application of LA for other diseases. However, it has been reported that LA induces insulin autoimmune syndrome (33).…”
Section: Discussionmentioning
confidence: 97%
“…These findings revealed a potential clinical application of LA for other diseases. However, it has been reported that LA induces insulin autoimmune syndrome (33).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, up to one half of patients with insulin autoimmune syndrome presented with a history of using drugs containing a sulfhydryl group, which include methimazole, α-mercaptopropionyl glycine, and glutathione within the previous year [13]. More recently, cases of insulin autoimmune syndrome caused by α-lipoic acid have been increasing, which has been attributed to the two sulfur atoms connected by a disulfide bond of α-lipoic acid, which generates a strong reducing power [14]. Based on these observations, insulin autoimmune syndrome is attributed to either methimazole or carbimazole, which is converted to methimazole in the body, in patients with Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hypoglycaemia with the use of ALA has been attributed to an autoimmune process called Insulin Autoimmune Syndrome (IAS), in addition to potentiating the effects of other hypoglycaemic agents like insulin therapy [82,83]. IAS (also known as Hirata's disease) was first described in 1970 and is a relatively rare cause of hypoglycaemia [84].…”
Section: Adverse Effectsmentioning
confidence: 99%